2007
DOI: 10.3324/haematol.10766
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new turbidimetric assay for von Willebrand factor activity useful in the general screening of von Willebrand disease

Abstract: We evaluated a new assay (HemosIL™VWF Activity on ACL-Futura) in the screening of VWD. Samples from healthy donors and previously diagnosed VWD patients were blindly analyzed by this new activity assay and standard VWF:RCo. Results agreed and both assays showed a similar sensitivity for the screening of VWD. Haematologica 2007; 92:5: 712-713 Von Willebrand disease (VWD), the most frequent inherited bleeding disorder, is caused by a deficiency and/or abnormality of the von Willebrand factor (VWF).1,2 The rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 8 publications
4
27
0
Order By: Relevance
“…As expected, and also reported by others, all of the new assays (i.e. VWF:GPIbR by the HemosIL latex agglutination assay and the HemosIL AcuStar assay , the VWF:GPIbM Siemens assay and the VWF:Ab assay ) performed well and yielded results close to the old reference standard VWF:RCo. Although statistically significant and consistent in all participating laboratories, the slightly steeper regression lines for the VWF:Ab and VWF:GPIbM were clinically insignificant.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, and also reported by others, all of the new assays (i.e. VWF:GPIbR by the HemosIL latex agglutination assay and the HemosIL AcuStar assay , the VWF:GPIbM Siemens assay and the VWF:Ab assay ) performed well and yielded results close to the old reference standard VWF:RCo. Although statistically significant and consistent in all participating laboratories, the slightly steeper regression lines for the VWF:Ab and VWF:GPIbM were clinically insignificant.…”
Section: Discussionsupporting
confidence: 89%
“…2,13 Results from VWF:Act assay have previously been shown to be well correlated with those of the standard VWF:RCo assay in all type 1 and 2 VWD variants. 7 Our retrospective study of 111 patients with well-identified VWD subtypes confirmed that VWF:RCo and VWF:Act are similar and well correlated. However, for certain patients, the results were very discordant with some cases of type 2M VWD being associated with normal VWF:Act.…”
Section: Discussionsupporting
confidence: 74%
“…The ristocetin‐dependent AcuStar assay is more sensitive to type 2 VWD than the ristocetin‐independent HemosIL LIA assay. It is also not influenced by rheumatoid factor (up to 800 units per mL), which can result in falsely high readings for LIA antigen and functional assays . The presence of anti‐mouse antibodies can also cause falsely high results in some antibody‐based assays , but in another case report, VWF:RCo[Acu] seemed less affected than some other assays .…”
Section: Discussionmentioning
confidence: 99%